Diet and cancer - Swapan Kumar Paul; Amrita Ghosh; Ranabir Pal; Shrayan Pal (Wolters Kluwer Medknow Publications, 2021)
Cancer arising out of diets and protective role of diet from cancers to preserve health and nutritional status is a debate in the healthcare arena. In search of perennial conflict on diet and cancer, researchers of this review emphasized conceptual and contextual details from commonly used dietary items and practices for optimum healthcare model. Twenty-four research studies were identified from 91 potentially relevant data bases and published literatures to collate an updated idea of diet and cancer. Studies were selected on, first; all emerging nutritional plans and related reports on cancer among published literature were sketchily searched. Second, "diet" and 'cancer control was also sourced from different journals, conference proceedings, and different media reports, Third, published reports from apex bodies of global importance like different professional national and international organizations were given due weightage. We have assembled diversity of opinion on prevention and control of cancer in different academic sources. Although there is no paucity of quantitative and qualitative data on diet and cancer, there is dearth of scientific and valid suggestions from scholars on this sensitive issue. In a holistic approach, we require more translational research about diet and cancer with definitive and conclusive evidences for day-to-day application in medical practice for the improvement in clinical approach of this complex debatable paradigm.